2015
DOI: 10.1155/2015/964392
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Peripheral Blood Count in Breast Carcinoma: Predictor of Prognosis or a Routine Test

Abstract: Background. Peripheral blood count is the first investigation to be done in every patient before surgery. As strong relationship exists between cancer and immune response of the body, clinical stage at presentation and altered hematological parameters can influence the progression of cancer and vice versa. Settings and Design. It is a case control study of total 50 cases (35 cases of carcinoma breast and 15 cases of benign breast disease). Methods. A case control study was carried out; 35 cases of breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
3
16
0
2
Order By: Relevance
“…[17][18][19] Many other scientists also observed changes in different stages of breast cancer. 15,[20][21][22] In the current study, we found that patients which were on radio-chemotherapy (both) had decreased mean values in all parameters as compared to individual therapies. Normally, blood cells are placed among the most rapidly dividing cells in the body and the most sensitive to chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[17][18][19] Many other scientists also observed changes in different stages of breast cancer. 15,[20][21][22] In the current study, we found that patients which were on radio-chemotherapy (both) had decreased mean values in all parameters as compared to individual therapies. Normally, blood cells are placed among the most rapidly dividing cells in the body and the most sensitive to chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 82%
“…14 Rana Singh AP et al also reported decrease in absolute lymphocyte count with increase in stage of carcinoma. 15 Ufelle SA et al reported significant decrease in all hematological parameters in breast cancer when compared with control. 16 This is in accordance with our study.…”
Section: Discussionmentioning
confidence: 96%
“…A case control studies carried out by Akinsegun [40] on breast cancer found 58 out 100 of the cases to be anaemic. However, [48] in a study to assess the perioperative blood count in breast carcinoma found no significant correlation between cancer patients and anaemia. Anaemia is associated with shorter survival in cancer patients and this association has been established for breast cancer and almost all types of cancer studied [18,[49][50].…”
Section: Discussionmentioning
confidence: 96%
“…Complete blood count reflects the response of cellular immunity in a patient with cancer [12]. The Erythopoietic indices of DMBA administered albino rats, given aqueous concentrate of the different plants is appeared on Table 1 & 2.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia is a common disease faced in cancer patients (such as cervical, ovarian, and endometrial cancer) and, as a result, anaemic patients suffer from shortness of breath, fatigue, and shrunk energy. Haemoglobin (Hb) and packed cell volume (PCV) are indirectly connected with raised risk of cardiac failure in cancer patients [12]. Furthermore, systemic inflammatory response has been identified to affect survival in a number of malignancies, of which white blood cells are key mediators in this response.…”
Section: Introductionmentioning
confidence: 99%